Approximate of differentiated functions by polynomials on regions with external peaks - Semenyuk , V. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
For isotropic Sobolev spaces defined on domains with outward cusps of power type, a method of approximation of functions and their derivatives by algebraic polynomials is indicated, and the corresponding approximation estimates are given.